PENERAPAN PENDEKATAN HUMANISTIK DALAM PEMBELAJARAN MATEMATIKA UNTUK MEMBANTU PEMAHAMAN KONSEP ABSTRAK PADA SISWA SD/MI - Via Zahrotun Nisa'; Alfi Nurur Rohmah; Najma Ata Amalia; Dian Mustika Anggraini (STKIP Subang, 2026)
Mathematics is an abstract subject that is often difficult for elementary school students to understand because it is not fully aligned with their cognitive development stage. Therefore, an appropriate learning approach is needed to help students understand mathematical concepts more easily and meaningfully. This study aims to examine the implementation of a humanistic approach in mathematics learning to help elementary school students understand abstract concepts. This study employed a qualitative approach using the library research method through the analysis of various relevant scientific sources, including journals, books, and previous studies. The findings indicate that the humanistic approach, which emphasizes student-centered learning, emotional involvement, and meaningful learning experiences, is able to create a comfortable learning environment and improve students' learning motivation. In addition, the use of contextual learning, concrete media, and experience-based learning strategies helps students connect mathematical concepts with everyday life, making abstract concepts easier to understand. The humanistic approach also contributes to increasing students' confidence, active participation, and positive attitudes toward mathematics learning. Thus, the humanistic approach is considered effective and meaningful in mathematics learning for elementary school students, both cognitively and affectively.